Development and mechanistic investigations into metal-catalysed cycloisomerisation of enynamides - Mekareeya, A (2017)
This thesis reports the work on investigations into the mechanism of palladium-catalysed enynamide cycloisomerisations (with Pd(OAc)2 / bis(benzylidene)ethylenediamine (bbeda) catalyst system in particular). Herein, it has been shown that the mechanism of this catalyst system is likely to proceed via a hydropalladation mechanism. In the course of study, we have uncovered the crucial influences of water, the pre-catalyst, and the ligand (bbeda) in this reaction. One of the key highlights is bbeda itself serves as a source of palladium(II) hydride during the reaction. In addition, kinetic isotope effects obtained from theoretical analysis are consistent with the experimental data. The computational studies also offer enhanced understanding in the stereoselectivity of the reaction...